Raw memory prijedor, an 'ethnic cleansing laboratory' - Wesselingh, Isabelle; Vaulerin, Arnaud (Saqi in association with the Bosnian Institute, 2005)
Since the end of the Bosnian war, in December 1995, more than 3,000 people have been declared missing, and more than 10,000 people who fled persecution have returned to resettle in Prijedor.Wesselingh and Vaulerin have produced a long and passionate enquiry, which not only reconstructs past events but attempts to understand how it is possible for anyone to return under the circumstances. What is left to say about the war today, and the crimes that were committed? Which memories ought to be preserved? Has justice been served? What is the role of the international community? Blending reportage, investigation and analysis, and containing interviews with refugees, camp survivors, war criminals and international agents, this is a tour de force that poses questions essential not only to the future of the former Yugoslavia but to all of Europe